1991
DOI: 10.1128/iai.59.1.51-58.1991
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ and CD8+ T lymphocytes both contribute to acquired immunity to blood-stage Plasmodium chabaudi AS

Abstract: In the present study, the contribution of CD4+ and CD8+ T lymphocytes to acquired immunity to blood-stage infection with the murine malaria species Plasmodium chabaudi AS was investigated. C57BL/6 mice, which are genetically resistant to infection with this hemoprotozoan parasite and exhibit a transient course of infection, were treated intraperitoneally with monoclonal antibodies to T-cell epitopes, either

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
7

Year Published

1992
1992
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 38 publications
3
58
0
7
Order By: Relevance
“…Second, T-cells are indispensable for acquiring immunity against blood-stage malaria as shown particularly in diverse murine malaria models such as P. chabaudi chabaudi, P. chabaudi adami, and P. yoelii (for reviews, see Weidanz & Long 1988, Good & Miller 1989, Langhorne et al 1989. Especially CD4+ T cells are of primary importance though B cells and/or CD8+ cells are also required (Jayawardena et al 1982, Meding & Langhorne 1991, Podoba & Stevenson 1991. Third, it has been reported that the adoptive transfer of T cells from immune mice does not help recipient mice to develop immunity against P. chabaudi under certain experimental conditions (McDonald & Phillips 1978, Favila-Castillo et al 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Second, T-cells are indispensable for acquiring immunity against blood-stage malaria as shown particularly in diverse murine malaria models such as P. chabaudi chabaudi, P. chabaudi adami, and P. yoelii (for reviews, see Weidanz & Long 1988, Good & Miller 1989, Langhorne et al 1989. Especially CD4+ T cells are of primary importance though B cells and/or CD8+ cells are also required (Jayawardena et al 1982, Meding & Langhorne 1991, Podoba & Stevenson 1991. Third, it has been reported that the adoptive transfer of T cells from immune mice does not help recipient mice to develop immunity against P. chabaudi under certain experimental conditions (McDonald & Phillips 1978, Favila-Castillo et al 1990.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmodium chabaudi AS was maintained by weekly passage in C57B1/6 mice as previously described [1]. For passage or infection of experimental animals, blood was collected via the retro-orbital plexus from two infected C57B1/6 mice and pooled.…”
Section: Parasitementioning
confidence: 99%
“…The importance of CD4^ T lymphocytes in the resolution ofa primary infection with blood-stage Plasmodium chahaudi has been established by the results of studies from our laboratory and others [1][2][3][4]. It would appear that these cells function during the early or acute phase ofthe infection in mediating the rapid decrease in peak parasitaemia to low or sub-patent chronic levels via antibody-independent cell-mediated meehanisms.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 This evidence strongly indicates that malaria-specific antibodies play a crucial role in protective immunity against malaria. Previous studies using a rodent model of malaria showed that CD4 + T-cell-depleted mice fail to control Plasmodium infection, [5][6][7][8] as is the case with interferon-c (IFN-c)-signalling-deficient mice. 2,[9][10][11][12][13] IFN-c-signalling-deficient mice may exhibit decreased dendritic cell activation and T helper type 1 (Th1) responses during infection.…”
Section: Introductionmentioning
confidence: 99%